An evolving trend in religious practices amongst Malaysian Hindus: A case study of shrines within the residence compound of Hindus, a new phenomenon? - Manimaran, S. (2014)
Hindus possess their own unique religious beliefs and practices and they have been inherited from one generation to another for centuries. Yet the religious beliefs and practices of Hindus living in India differes from that of Hindus living elsewhere or outside India. The best exemplification of the differences is the religious practice of Malaysian Hindus as they have introduced a new trend in the Hindu religious practice by building shrines for deities within their residence compound. Itis a new phenomenon amongst the Malaysian Hindu community and also it is envisaged as a problem in the nation as most shrines built illegally without the consent of the local authorities. This article aims at looking at the new phenomenon prevalent amongst present day Malaysian Hindus and how the phenomenon emerged in the society.